The institution of the ‘Ulama’: origin and early development in the formative period - Gilani, Sayyid Muhammad Yunus (University of Peshawar, 2010)
There is no religious hierarchy or priestly class in Islam. However, despite the absence of any church, priests and sacraments1, with the passage of time there emerged in the Muslim world a class of religious luminaries who possessed legislative, social and political authority. These scholars or religious leaders govern almost all the aspects of the human life for at least in theory; the religion and community are inseparable in Islam.2 They interpret the Qur’an and the Suunah, and need be, derive laws from these sources. They also make entirely new rules based on analogy to meet the challenges of the contemporary world, provided they do not violate Qur’an and Sunnah. They may have expertise in any of the disciplines, but collectively they are known as „Ulama‟. The present article attempts to trace the origin and early development of this institution of „Ulama‟. A review of the existing literature leaves room for and demands for this direct and detailed historical, etymological & critical study of this institution in the context of academic, social, juristic and legislative functions